Alternative dynamic torsion test to evaluate the elastic modulus of polymers - Piedade, Lucas Pereira [UNESP] (2020)
This work presents an alternative for the determination of the torsion modulus, G, of polymers. These materials may be subjected to shear stresses in some structural applications; thereby, the knowledge of G is of great interest. For this purpose, a mechanical system featuring a simplified torsion pendulum version and a rotational motion sensor (RMS) coupled to it was used to establish an angular position as a function of time. The applied technique is considered non-destructive and makes it possible to obtain G without the Poisson's ratio through an equation derived from mechanical spectroscopy and material strength. The main goal is to present and validate the employment of this method for polymers. Therefore, circular cross-sectional samples of extruded polytetrafluoroethylene (PTFE) were subjected to torsional stresses, in which a physical and quantitative explanation is given for the frequency and G curves as a function of the prefixed rotational inertia (I), length (L), and diameter (d). Differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) were also made to ensure the reliability of data. It is possible to establish an L/d ratio, which explains why G converges to a single value when the sample dimensions are different from each other. It was found that G is approximately 350 MPa for an L/d ratio equivalent to 10.64. Such a value is within limits found in the literature, opening the possibility of assessing other polymers.